Effects of osthole and Bacillus amyloliquefaciens on the physiological growth of Panax quinquefolius in a forest - Jiang, Jinhui; Fan, Guangxiong; Wen, Rong; Liu, Tao; He, Shuran; Yang, Shengchao; Zi, Shuhui (Frontiers in Microbiology, 2024)
IntroductionThe biological activities of osthole have been widely reported in recent years. However, few studies have been conducted on osthole in agriculture, and its effects on plant growth have little been reported.MethodsThree experimental treatments were set up in this experiment: blank control (CK), osthole (CLS), and B. amyloliquefaciens (LKWS). In this study, the effects of osthole and Bacillus amyloliquefaciens on the growth parameters, photosynthesis, antioxidant enzyme activities, disease incidence, and microbiome of forested P. quinquefolius were tested.ResultsThis study demonstrates that the use of osthole and B. amyloliquefaciens significantly improved the growth of Panax quinquefolius in a forest compared to that in the control treatment, increased the total chlorophyll and carotenoid content of P. quinquefolius, significantly increased its net photosynthetic rate, and decreased the stomatal conductance and intercellular CO2 levels. In addition, the use of osthole and B. amyloliquefaciens significantly improved ascorbate peroxidase and peroxidase (POD) activities, enhanced antioxidant activities of the P. quinquefolius POD, and reduced the disease incidence and index of American ginseng anthracnose. Based on the American ginseng microbiome analysis, the use of osthole and B. amyloliquefaciens could change the structure of the American ginseng microbial community, significantly increase the diversity of American ginseng bacteria, significantly decrease the diversity of American ginseng fungi, stimulate the recruitment of more growth-promoting microorganisms to American ginseng, and build a more stable microbial network in American ginseng.DiscussionIn conclusion, we found that the application of osthole had a positive effect on the growth of American ginseng, providing a theoretical basis for its subsequent application in agriculture.